2020
DOI: 10.1111/imj.14980
|View full text |Cite
|
Sign up to set email alerts
|

A case of broken heart syndrome via the telephone: socially distant outpatient clinics in the COVID‐19 pandemic

Abstract: A case of broken heart syndrome via the telephone: socially distant outpatient clinics in the COVID-19 pandemic A 69-year-old woman presented to the emergency department with central dull chest pain. Electrocardiography revealed Q waves and ST elevation in the inferior leads and cardiac troponin I was elevated at 1506 ng/L (normal range <10). She was taken for emergent coronary angiography, which demonstrated chronic occlusion of her right coronary artery, left ventricular ejection fraction of 34% and basal hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…After applying the eligibility criteria and title and abstract review followed by detailed evaluations, 67 articles were selected. 4 , 5 , 9 , 11 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After applying the eligibility criteria and title and abstract review followed by detailed evaluations, 67 articles were selected. 4 , 5 , 9 , 11 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , ...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 1064 studies were identified. After applying the eligibility criteria and title and abstract review followed by detailed evaluations, 67 articles were selected 4,5,9,11,18–80 . Of these articles, 46 were centered around TTS in patients with COVID‐19, 13 were related to TTS in patients with emotional triggering events, and 8 were linked to TTS in patients with recent COVID‐19 vaccination (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Key issues raised are the lack of physical examination, lack of non‐verbal cues and the dependence on technology and adequate Internet connection that can be challenging. With TP use, there are also perceived challenges that come with not having visual rapport or connection with a patient and the impact this may have on a consultation 13 . However, for healthcare professionals, telemedicine can provide the opportunity for more flexible work practices, ease pressure on administration staff as well as assist patients and doctors alike in reducing travel times and breaking down geographical barriers.…”
Section: Discussionmentioning
confidence: 99%
“…With TP use, there are also perceived challenges that come with not having visual rapport or connection with a patient and the impact this may have on a consultation. 13 However, for healthcare professionals, telemedicine can provide the opportunity for more flexible work practices, ease pressure on administration staff as well as assist patients and doctors alike in reducing travel times and breaking down geographical barriers. 4 (0.3%) 1 (0.3%) 0.931 0.759 †Multiple regression performed to adjust for baseline differences of age, gender, English as first language, rural status, initial appointment status and cardiologist seen.…”
Section: Discussionmentioning
confidence: 99%